Nilai-Nilai Pendidikan Islam Dalam Pembacaan Assalai/Asyroqol Pada Masyarakat Melayu Sambas di Dusun Semayong Desa Sungai Kumpai - Nurul; Suhari; Suriadi (Jurnal Ilmu Sosial dan Humaniora, 2023)
The Sambas Malay community in Semayong Hamlet, Sungai Kumpai Village still carries out the tradition of reciting assalai/asyroqol which is considered to complement the events they hold. Reading assalai/asyroqol in Semayong Hamlet, Sungai Kumpai Village seems to be an obligation that is not formally written down. However, only older people are involved in reading assalai/asyroqol, even though assalai/asyroqol itself is a tradition that is acculturated to Islamic culture. Starting from the existing problems, the focus of this research problem is to describe the values ​​of Islamic education in reading assalai/asyrqol and their relevance to the Sambas Malay community in Semayong Hamlet, Sungai Kumpai Village. This research uses qualitative methods with descriptive research type. The data collection techniques used in this research are observation techniques, interview techniques and documentation techniques. Researchers used observation techniques to observe phenomena related to the reading of assalai/asyroqol in Semayong Hamlet, Sungai Kumpai Village. Meanwhile, researchers used interview techniques to dig up deeper information regarding the issue of Islamic educational values ​​in reading assalai/asyroqol. Furthermore, researchers used documentation techniques to obtain additional data to complement the data obtained through observation and interview methods. Based on the results of observations and interviews as well as documentation, the results of this research are: 1) The values ​​of Islamic education in reading assalai/asyrokol in the Sambas Malay community in Semayong Hamlet, Sungai Kumpai Village, namely: a) The values ​​of the faith consist of: reading Surah Al-Fatihah, reading salawat and praying; b) Sharia values ​​consist of: friendship and cooperation; c) Moral values ​​consist of discipline and respect for knowledgeable people. 2) The relevance of the values ​​of Islamic education in reading assalai/asyrokol to the Sambas Malay community in Semayong Hamlet, Sungai Kumpai Village, namely: increasing faith in Allah and His Messenger, as a medium for friendship, and habituation of commendable behavior.